The Analysis of Hyperbole Found in Live in the Lou Album by Story of the Year - Florensiana Yesatria Lasman (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2025)
This study aims to examine the use of hyperbole in Story of the Year’s album, Live in the Lou, with an emphasis on its role in enhancing emotional expression and the intensity of the lyrical message. Specifically, this study will identify various manifestations of hyperbole in song lyrics, classify the types used, and analyze their meaning and communicative function within the narrative and musical context of each song. The method used in this study is descriptive qualitative, focusing on textual analysis of the song lyrics. The theory of figurative language, particularly hyperbole, is applied to analyze the data. The results show that hyperboles are frequently used to convey intense feelings such as love, anger, pain, and despair. These exaggerations help the band express emotional depth and connect with listeners on a personal level. It is concluded that hyperbole plays a significant role in enhancing the aesthetic and emotional value of the songs in the album.